Long noncoding RNA landscapes specific to benign and malignant thyroid neoplasms of distinct histological subtypes - Valentina D. Yakushina (Nature Portfolio, 2021)
Abstract The main types of thyroid neoplasms, follicular adenoma (FA), follicular thyroid carcinoma (FTC), classical and follicular variants of papillary carcinoma (clPTC and fvPTC), and anaplastic thyroid carcinoma (ATC), differ in prognosis, progression rate and metastatic behaviour. Specific patterns of lncRNAs involved in the development of clinical and morphological features can be presumed. LncRNA landscapes within distinct benign and malignant histological variants of thyroid neoplasms were not investigated. The aim of the study was to discover long noncoding RNA landscapes common and specific to major benign and malignant histological subtypes of thyroid neoplasms. LncRNA expression in FA, FTC, fvPTC, clPTC and ATC was analysed with comprehensive microarray and RNA-Seq datasets. Putative biological functions were evaluated via enrichment analysis of coexpressed coding genes. In the results, lncRNAs common and specific to FTC, clPTC, fvPTC, and ATC were identified. The discovered lncRNAs are putatively involved in L1CAM interactions, namely, pre-mRNA processing (lncRNAs specific to FTC); PCP/CE and WNT pathways (lncRNAs specific to fvPTC); extracellular matrix organization (lncRNAs specific to clPTC); and the cell cycle (lncRNAs specific to ATC). Known oncogenic and suppressor lncRNAs (RMST, CRNDE, SLC26A4-AS1, NR2F1-AS1, and LINC00511) were aberrantly expressed in thyroid carcinomas. These findings enhance the understanding of lncRNAs in the development of subtype-specific features in thyroid cancer.